Проблеми розвитку управління ресурсним потенціалом будівельних організацій - Синиця, М. М. (Ways to Improve Construction Efficiency, 2014)
At present, the development of management systems is one of the most important ways to increase resource capacity building organizations. Existing estimates are overwhelmingly based on several approaches, based on this key issue is to develop criteria for the optimality of control and patterns of its use in a variety of individual problems. Therefore, to evaluate the effectiveness of the functioning of any system of governance and its compliance with the requirements of the modern state must have a general criterion, as highlighted in the article. Some incremental techniques and proven effectiveness that the successful functioning of any modern building management systems in their specificity must be enabled human.